Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT Food Station Jakarta - Sidqi Dani Anansyah; Arry Dwi Syahputra (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
The Purpose to analyze the influence of work motivation and work environment on employee performance at PT Food Station Jakarta. This research is included in the category of causal associative research using a quantitative approach. The population in this study were employees of PT Food Station Jakarta. Using the Slovin formula. The technique used for sampling is simple random sampling. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways work motivation and work environment have a positive and significant effect on employee performance at PT Food Station Jakarta.